Does the Degree of Maternal Fever in the Setting of Chorioamnionitis Lead to Adverse Neonatal Outcomes? - Megan S. Varvoutis; Azza E. Abdalla; Sarah K. Dotters-Katz (Thieme Medical Publishers, Inc., 2022)
Abstract Objective The effect of the degree of maternal fever in the setting of chorioamnionitis on neonatal morbidity is unclear. The objective of this study is to assess the association between high maternal fevers (≥ 39°C) on neonatal morbidity. Study Design Secondary analysis of Maternal-Fetal Medicine Units (MFMU) Cesarean Registry data obtained from 1999 to 2002 among singleton gestations with chorioamnionitis. Women with a temperature less than 39°C (low fever) compared with those with greater than or equal to 39°C (high fever). Primary outcome was a composite of adverse neonatal outcomes such as death, sepsis, necrotizing enterocolitis, grade-3 or -4 intraventricular hemorrhage, seizure within 24 hours of delivery, intubation within 24 hours of delivery, and requiring cardiopulmonary resuscitation. Demographic characteristics compared using Fisher's exact and Wilcoxon's rank-sum test as appropriate. Multivariate logistic regression analysis with performed to control for cofounders. Stratified analysis also performed to assess outcomes in term infants. Results Of 1,313 included women, 1,200 (91.3%) were in the low fever group and 113 (8.7%) were in the high fever group. Women in the high fever group were more likely to be African American and group B Streptococcus positive. No difference in primary outcome was noted between the groups (38.9% high fever vs. 35.8% low fever, p = 0.54). High maternal fever was associated with increased risk of NICU admission (48.1 vs. 50.4%, p = 0.02). When controlling for African American race, preterm birth, and delivery route, patients with high fever were not more likely to have adverse neonatal outcomes (adjusted odds ratio [aOR] = 1.28, 95% confidence interval [CI]: 0.84, 1.98). In the analysis limited to term infants, when controlling for confounders, high fever, similarly, was not associated with increased odds of adverse neonatal outcomes (aOR = 1.59, 95% CI: 0.96, 2.65). Conclusion The degree of maternal fever does not appear to be associated with an increased likelihood of adverse neonatal outcomes. Better understanding maternal factors that affect neonatal morbidity in the setting of chorioamnionitis is critical. Key Points High maternal fever in the setting of chorioamnionitis does not appear to have an increased likelihood of adverse neonatal outcomes. It is important to identify factors that may increase the risk of adverse outcomes such as early onset sepsis. Maternal fever may not be a strong indicator for neonatal outcomes and antibiotic protocols.